2020
DOI: 10.1371/journal.pone.0227003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteome profiling of freshwater and seawater life stages of rainbow trout (Oncorhynchus mykiss)

Abstract: The sea-run phenotype of rainbow trout (Oncorhynchus mykiss), like other anadromous salmonids, present a juvenile stage fully adapted to life in freshwater known as parr. Development in freshwater is followed by the smolt stage, where preadaptations needed for seawater life are developed making fish ready to migrate to the ocean, after which event they become post-smolts. While these three life stages have been studied using a variety of approaches, proteomics has never been used for such purpose. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 117 publications
(132 reference statements)
0
8
0
Order By: Relevance
“…( 17 )). Recent work has applied such approaches in salmonids ( 18 ), including to document changes in plasma protein abundance during sea water adaptation in rainbow trout ( 19 ). Such approaches require a comprehensive protein database for the target species and enable simultaneous identification and quantification of hundreds to thousands of proteins per experiment ( 20 – 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 17 )). Recent work has applied such approaches in salmonids ( 18 ), including to document changes in plasma protein abundance during sea water adaptation in rainbow trout ( 19 ). Such approaches require a comprehensive protein database for the target species and enable simultaneous identification and quantification of hundreds to thousands of proteins per experiment ( 20 – 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even if previous studies have shown gene expression changes when fish adapt to water salinity change (e.g. migration, precipitation) for salmonids (Morro, 2020;Norman et al, 2014) and other species (Fiol, 2006;Pujante, 2018), evidence of such an impact of low water salinity on the overall ovulatory process were, to our knowledge, previously unreported. This raises the question of how low water salinity can inhibit the overall ovulatory process and not only osmotic exchanges.…”
Section: Inflammation-related Genes Are Under-expressed In Low Salinity Watermentioning
confidence: 68%
“…To overcome these limitations, in this study we applied MS-based proteomics to nurse shark plasma to identify the proteins present and quantify abundance changes following immunization. Most proteomic studies rely upon an annotated, species-matched genome as the reference database for protein identification (e.g., 13 , 14 , 27 ). As the nurse shark genome has yet to be sequenced, we compared two alternate approaches for protein identification.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous immunization study on rainbow trout ( Oncorhynchus mykiss ), also using LC-MS/MS proteomics ( 14 ), identified abundance changes in 278 plasma proteins, including both classical immune proteins (e.g., complement components) and proteins not usually associated with immune responses in mammals (e.g., apolipoproteins). A separate study by Morro and colleagues ( 27 ) identified a greater number of plasma proteins (1822) in rainbow trout using LC-MS/MS label-free proteomics in combination with enrichment of low abundance proteins. We therefore hypothesized that the approach used in our previous study would yield similar results in terms of the number and types of immune proteins detected in nurse shark.…”
Section: Introductionmentioning
confidence: 99%